Knowledge construction and sharing in a networked collaborative environment - Mat Daud, Nuraihan (2013)
To stay informed, teachers would have to make a conscious effort to continue learning. In a networked environment, collaborative approach can be adopted for the purpose of knowledge sharing and knowledge construction. Web 2.0 and 3.0 technologies make possible peer interaction in a more systematic way. Teachers’ practical knowledge of the nature and know-how of interaction on social networks may give them ideas on how to apply the technologies in their classroom. The issue remains to what extent have these technologies been used to the best advantage of both students and teachers. This paper presents possibilities for collaborative works among teachers and students within and among different institutions. The paper emphasizes how the technologies can be used to conduct collaborative tasks outside the classroom, and in an authentic context. It demonstrates how facilities such as Second Life, Google Documents and Dropbox can be used to promote international collaboration. It also emphasizes the need to adopt the associated pedagogical practices when adopting the technologies in a classroom.